Microscopic Characteristics Of Emu (Dromaius Novaehollandiae) Semen Collected By Non-Teaser Method In Humid Tropical Climate - Sundaresan, A.; Omprakash, A.V.; Ezhilvalavan, S.; Pandian , C. (Indian Journal of Veterinary Sciences and Biotechnology, 2015)
A study was conducted for collection and evaluation of Emu bird semen by non teaser method. The raw semen collected from individual Emu birds was evaluated for microscopical seminal attributes. Highly significant (P
Keywords: Emu; Semen; Evaluation; Non Teaser method